2017
DOI: 10.3892/ijmm.2017.3349
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen receptor‑β‑dependent effects of saikosaponin‑d on the suppression of oxidative stress‑induced rat hepatic stellate cell activation

Abstract: Saikosaponin-d (SSd) is one of the major triterpenoid saponins derived from Bupleurum falcatum L., which has been reported to possess antifibrotic activity. At present, there is little information regarding the potential target of SSd in hepatic stellate cells (HSCs), which serve an important role in excessive extracellular matrix (ECM) deposition during the pathogenesis of hepatic fibrosis. Our recent study indicated that SSd may be considered a novel type of phytoestrogen with estrogen-like actions. Therefor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 44 publications
0
18
0
Order By: Relevance
“…In addition, our previous study reported that SSd was a new kind of phytoestrogen, which could suppress the proliferation and activation of hepatic stellate cells through modulation of estrogen receptor β. 30,31 Therefore further studies are still needed to explore the specific action mechanisms of SSd.…”
Section: Il-1βmentioning
confidence: 99%
“…In addition, our previous study reported that SSd was a new kind of phytoestrogen, which could suppress the proliferation and activation of hepatic stellate cells through modulation of estrogen receptor β. 30,31 Therefore further studies are still needed to explore the specific action mechanisms of SSd.…”
Section: Il-1βmentioning
confidence: 99%
“…Oxidative stress serves a crucial role in inducing HSC activation and fibrogenic potential ( 16 ). Superoxide dismutase (SOD), one of the most important protective enzymes, provides the first antioxidant defense system in various organs and tissues, including the liver ( 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…4A, the HSCs from CCl 4 mice exhibited a markedly decreased expression of ER-α, and ER-β, and GPER1, while SSd treatment rescued ER-β and GPER1 expression in primary HSCs. Here we focused on the correlation of SSd with GPER1 because the regulatory role of SSd in ER-β has been verified in our previous studies [30]. The results from qPCR and Western blot analysis showed that TGF-β treatment reduced the mRNA and protein expression of GPER1 in LX-2 cells, whereas SSd treatment reversed the effect (Fig.…”
Section: Ssd Repressed Hscs Autophagy Activation By Regulating Gper1mentioning
confidence: 65%
“…Our previous studies have demonstrated that SSd represses oxidative stress-induced HSCs activation by regulating estrogen receptor (ER)-β [30]. Given the important role of Estrogens in repressing HSCs activation and liver fibrosis by interacting with its nuclear receptors (ER-α, and ER-β) and membrane receptor (G protein-coupled estrogen receptor, GPER1) [31], we next investigated whether SSd exerted its anti-liver fibrotic function by regulating estrogen receptors expression.…”
Section: Ssd Repressed Hscs Autophagy Activation By Regulating Gper1mentioning
confidence: 99%